Keratometric astigmatism evaluation after trabeculectomy - Kumari, Rashmi; Saha, BC; Puri, LR (Nepalese Journal of Ophthalmology, 2013)
Introduction: Post-operative astigmatism is one of the most important causes for diminution of vision after trabeculectomy. Objective: To evaluate the induced corneal astigmatism following trabeculectomy with the use of 8-0 silk suture. Materials and methods: A prospective interventional study was done including 100 consecutive eyes of 84 patients who underwent trabeculectomy with the use of 8-0 silk suture. The postoperative induced astigmatism on the 1st post-operative day, 3rd week and after 6 months was determined. Statistics: Vector analysis was performed on the data using a computerized method for calculating the surgically induced astigmatism (SIA) for each eye at every time point postoperatively. In order to analyze group changes, we also performed vector decomposition which gave us a mathematical expression of the changes in astigmatism “with the rule” (WTR) or “against the rule” (ATR). Results: The mean age of all the patients was 53.31 11.39 years. The mean 1st post-operative surgically induced astigmatism (SIA) was 2.73 D ( 99 degree ) which reduced to 0.41 D ( 58 degree) at the 3rd week and 0.43 ( 21 degree) at 6 months. The mean WTR astigmatism was 4.46 D and ART astigmatism was 1.42 D on the 1st post-operative day which was significantly high ( p<0.0001). At the 3rd week and 6 months WTR astigmatism ( 1.40 D and 1.08D ) and ATR astigmatism (1.27 D and 1.10 D) showed no significant changes (p=0.69,0.97 respectively. Conclusion: Trabeculectomy with the use of 8/0 silk sutures showed significantly high 1st post-operative day SIA which nevertheless perished fast to a minimum amount at just 3 weeks. Nepal J Ophthalmol 2013; 5(10): 215-219 DOI: http://dx.doi.org/10.3126/nepjoph.v5i2.8731